Development and Validation of Psychosocial Problem Assessment Instruments in Critical Patients in the Intensive Care Unit (ICU) - Hermala Dewi, Nelly (Media Publikasi Cendekia Indonesia, 2025)
The assessment of psychosocial problems is an important component of determining patient needs in managing therapy and providing comprehensive care for patients in the ICU. Until now, there has been no specific instrument to measure the psychosocial problems of critical patients. This study aimed to develop and validate an instrument to assess psychosocial problems. This research used a quantitative design, testing 104 ICU nurses and 38 patients by questionnaire; in two hospitals in Banten, those who passed obtained ethics approval. Data were collected from May to July 2024. Data analysis in this study used Confirmatory Factor Analysis (CFA) with Lisrel 8.5. to test the construct validity and reliability based on the content and language suitability and univariate testing to describe the result of experienced psychosocial problems to patients. The result is the instrument developed five indicators: anxiety, depression, hopelessness, helplessness, and deprivation. All indicators were declared valid and reliable using Measurement by Standardized Loading Factor (SLF), Construct Reliability (CR), and Average Variance Extracted (AVE), and good model fit in SEM analysis and testing to critical patients in the ICU found that some patients experienced severe anxiety was 19 (50.0%) respondents, mild to moderate deprivation was 27 (71.1%) respondents, mild to moderate depression was 22 (57.9%) respondents, severe helplessness was 21 (55.3%) respondents, and mild to moderate hopelessness was 20 (52.6%) respondents. The conclusion of this research is that this instrument has been evolved and declared valid and reliable